AVNeo improves early haemodynamics in regurgitant bicuspid aortic valves compared to aortic valve repair. (26th August 2022) - Prinzing, Anatol; Böhm, Johannes; Sideris, Konstantinos; Vitanova, Keti; Lange, Rüdiger; Krane, Markus
Abstract: OBJECTIVES: Calcified or fibrotic cusps in patients with bicuspid aortic valves and aortic regurgitation complicate successful aortic valve (AV)-repair. Aortic valve neocuspidization (AVNeo) with autologous pericardium offers an alternative treatment to prosthetic valve replacement. We compared patients with regurgitant bicuspid valves undergoing AV-repair or AVNeo. METHODS: We retrospectively analysed patients with regurgitant bicuspid valves undergoing AV-repair or AVNeo. We focused on residual regurgitation, pressure gradients and effective orifice area, determined preoperatively and at discharge. RESULTS: AV-repair was performed in 61 patients (mean age: 43.2 ± 11.3 years) and AVNeo in 22 (45.7 ± 14.1). Prior to the operation patients of the AV-repair group showed severe regurgitation in 38 cases (62.3%) and moderate in 23 (37.6%); in the AVNeo group, all patients exhibited severe regurgitation. Postoperatively, 57 patients (93.4%) patients had no or mild regurgitation after AV-repair and 21 (95.4%) after AVNeo. In AVNeo-patients, peak (10.6 ± 3.1 mmHg vs 22.7 ± 11 mmHg, P < 0.001) and mean pressure gradients (5.9 ± 2 mmHg vs 13.8 ± 7.3 mmHg, P < 0.001) were significantly lower and the orifice area significantly larger (2.9 ± 0.8 cm 2 vs 1.9 ± 0.7 cm 2, P < 0.001) compared to repair. CONCLUSIONS: Compared to AV-repair, patients AVNeo showed lower mean pressure gradients and larger orifice areas at discharge. The functional result was not different. Abstract : In recent years, aortic valve repair (AV-repair) evolved into a treatment alternative for patients with insufficient aortic valves [1].